A Battle Royal: Service Work Activism and the 1961-1962 Royal York Strike - Milloy, Jeremy (Labour/Le Travailleur, 2006)
Abstract Although service work occupies an increasingly central position in the Canadian labour market, its legacy of activism has largely been forgotten by scholars.This paper begins a reclamation of that legacy by analysing the bitter 1961-1962 strike at the Royal York Hotel in Toronto, Canada's most luxurious lodgings. The unsuccessful battle of mostly immigrant workers against a powerful corporation anticipates the multinational consolidation of and asymmetrical struggle in the industry over the next four decades. The paper evaluates strategies used by service workers, explores the different historical dynamics of service-work trade unionism, analyses the cultural contests which sprang up around such a powerful symbolic action, and seeks to explain what lessons have been learned by current Toronto hotel activists. It represents one starting point in the important work of understanding service work activism, and the economic, political, and cultural battles around class, gender, ethnicity, and consumption in Canada.